2022
DOI: 10.21037/qims-20-1388
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of qualitative MRI in 550 paediatric brain tumours: evaluating current practice in the computational era

Abstract: Background: To investigate the accuracy of qualitative reporting of conventional magnetic resonance imaging (MRI) in the classification of paediatric brain tumours.Methods: Preoperative MRI reports of 608 children prior to resection or biopsy of an intracranial lesion were retrospectively reviewed. A total of 550 children had complete radiological and histopathological notes, thereby reaching our inclusion criteria. Concordance between MRI report and final histopathological diagnosis was assessed using an esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…It should however be considered that the supratentorial categorization of the tumors is slightly different in these two studies. Our results also agree with the report by Dixon et al, 7 in that tumors in the posterior fossa were easier to diagnose.…”
Section: Location Of the Tumorssupporting
confidence: 93%
See 2 more Smart Citations
“…It should however be considered that the supratentorial categorization of the tumors is slightly different in these two studies. Our results also agree with the report by Dixon et al, 7 in that tumors in the posterior fossa were easier to diagnose.…”
Section: Location Of the Tumorssupporting
confidence: 93%
“…The latter have not been reported earlier. The results for the supratentorial tumors obtained in this study show the potential of deep learning models 9/13 trained on MRI data for supporting radiologists and improving the diagnosis of pediatric supratentorial tumors which have been shown to be hard to classify 7 . It should however be considered that the supratentorial categorization of the tumors is slightly different in these two studies.…”
Section: Location Of the Tumorsmentioning
confidence: 74%
See 1 more Smart Citation
“…[4][5][6][7] These methods rely on accelerating data acquisition using parallel imaging [8], compressed sensing [9][10][11][12][13], non-Cartesian imaging [14], and simultaneous multi-slice imaging. [15] Quantitative imaging: Dixon et al [16] analyzed 550 pediatric patients with brain tumors and showed the accuracy of qualitative diagnostic imaging. Consequently, quantitative MR (qMR) imaging plays a crucial role in diagnosing.…”
Section: Introductionmentioning
confidence: 99%
“…Dixon et al [16] analyzed 550 pediatric patients with brain tumors and showed the accuracy of qualitative diagnostic imaging. Consequently, quantitative MR (qMR) imaging plays a crucial role in diagnosing.…”
Section: Introductionmentioning
confidence: 99%